(untitled) (Palíndromo, 2021)
In this article, I show drawings in which the initial sense was to restore spatial memory based on an iconographic set of travel photographs, images stored in folders and postcards. This work took place during the period from march to December of the year 2020. The article states that the images can materialize in rhythmic and sensitive montages, being therefore, dialectical. Sensitive in the artistic sense, in the willingness to express a phenomenology of the active and dialectical image as a rhythmic phenomenon, which takes place at a certain historical or biographical moment and which demonstrates anthropological, memorial, conflictual and gestural intelligibility.